An analysis of the intention of female pharmacy students to work in community pharmacy settings in Saudi Arabia using the theory of planned behavior - Ahmed M. Alshehri; Wafa H. Alqahtani; Aljoharah A. Moaili; Yasser S. Almogbel; Ziyad S. Almalki; Abdullah K. Alahmari; Ahmed A. Albassam; Nehad J. Ahmed (Elsevier, 2024)
Objective: This study aimed to determine the intention of female Saudi pharmacy students to work in community pharmacies and the factors associated with this intention. Methods: This cross-sectional study was conducted between April 2022 and June 2022 and included female students from pharmacy colleges in Saudi Arabia. The survey was created based on the Theory of Planned Behavior. It included items that measure student intentions, attitudes, subjective norms, and perceived behavioral control regarding working in community pharmacies in Saudi Arabia. The study also included items that assessed sociodemographic characteristics, pharmacy program degrees, training, and job preferences of students. Results: A total of 407 participants completed the survey. The average age was 21.8 (±1.6) years, and most participants were Saudi nationals (97.79 %). The intention of participants to work in community pharmacies after graduation was low (mean = 3.2 ± 1.8; range: 1-7). Slightly positive attitudes toward working in a community pharmacy after graduation were revealed as participants showed an overall attitude mean of 4.5 ± 1.6 (range: 1-7). Furthermore, the participants perceived a low social pressure toward working in a community pharmacy after graduation (mean of 3.3 ± 1.9; range: 1-7). The intention of female pharmacy students to work in community pharmacies was significantly predicted by attitudes (p-value < 0.0001), perceived behavioral control (p-value = 0.0017), nationality (p-value = 0.0151), residence in the Saudi Arabian region (p-value = 0.0013), monthly income (p-value = 0.0231), pharmacy degree program (p-value = 0.0035), training received in community pharmacies (p-value = 0.0145), had a relative working in a community pharmacy (p-value = 0.0257), and preference to work in community pharmacies after graduation (p-value = 0.0001). Conclusion: Female pharmacy students in Saudi Arabia had a low intention to work in community pharmacies, a positive attitude toward working in community pharmacies, and perceived no social pressure to work in them. A positive attitude and behavioral perception of control toward working in community pharmacies were demonstrated among pharmacy students who study at a university outside Riyadh, undertaking a bachelor's degree in pharmacy, have a monthly income higher than 5000 Saudi riyals (USD 1,333.3), previously received training in community pharmacies, having a relative working in a community pharmacy, prefer to work in community pharmacies after graduation.